Teachers' Readiness in Early Childhood Inclusion Education Reviewed from the Difference in Efficacy Values and Teachers' Teaching Experience - Isma Nasikhatin Nafiah; Diana; Yuli Kurniawati Sugiyo Pranoto (Postgraduate, University of Mataram, 2025)
The purpose of this study was to determine the readiness of teachers in inclusive education for early childhood in terms of differences in teacher efficacy values and teaching experience. This study uses a quantitative approach with a correlational design. The population in this study is 30 PAUD teachers in Semarang City. Data collection techniques using questionnaires. The statistical analysis process was carried out using the IBM Statistical Program for Social Science (SPSS) for windows version 26 computer program. The results of the study indicate that the level of teacher efficacy plays an important role in determining their readiness to implement inclusive education in PAUD in Semarang City. The novelty of this study lies in the focus of research on the readiness of early childhood teachers by considering differences in their efficacy and experience values. This can provide a deeper understanding of how early childhood educators face challenges in the environment.